The Influence of Internal Control and Good Corporate Governance Implementation on Fraud Prevention - Rahayu, Yuli Sri; Soemantri, Roebiandini; Irawady, Cahya (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
This research is motivated by the many cases of fraud in the banking sector in Indonesia. The results of the 2019 Indonesian Fraud Survey stated that the fraud that occurred was caused by internal control factors and the implementation of good corporate governance. This research aims to determine the influence of internal control and the implementation of good corporate governance on fraud prevention in general banking in The research method used in this research is the verification method. The population in this research are internal auditors who work at commercial banks in the Jakarta and Bandung areas. The sampling technique used was a probability sampling technique with a simple random sampling technique, and used the Slovin formula so that the total sample was 47 internal auditors in the Jakarta and Bandung areas The data analysis used is multiple linear regression analysis using the SPSS program. Research results Simultaneously, Internal Control and the implementation of Good Corporate Governance have an effect on fraud prevention. Partially, the implementation of internal control has an effect on fraud prevention. Partially, the implementation of good corporate governance has an effect on prevention